Completion at the Expense of Access? The Relationship Between Performance-Funding Policies and Access to Public 4-Year Universities. (June 2020) - Gándara, Denisa; Rutherford, Amanda
Efforts to improve college-completion rates have dominated higher education policy agendas. Performance-based funding (PBF) intends to improve college completion and links state funding for public colleges and universities to performance measures. One critique of PBF policies is that institutions might restrict student access. This study uses a difference-in-differences design and institution-level data from 2001 to 2014 to examine whether 4-year, public institutions become more selective or enroll fewer underrepresented students under PBF. Our findings, supported by various robustness checks, suggest that institutions subject to PBF enroll students with higher standardized test scores and enroll fewer first-generation students. PBF models tied to institutions' base funding are more strongly associated with increased standardized test scores and enrollment of Pell students.